Megadisasters : the science of predicting the next catastrophe - Diacu, Florin, 1959-2018. (Princeton, N.J. : Princeton University Press, 2010)
Each chapter of this exciting and eye-opening book explores a particular type of cataclysmic event and the research surrounding it, including earthquakes, tsunamis, volcanic eruptions, hurricanes, rapid climate change, collisions with asteroids or comets, pandemics, and financial crashes. Florin Diacu tells the harrowing true stories of people impacted by these terrible events, and of the scientists racing against time to predict when the next big disaster will strike. He describes the mathematical models that are so critical to understanding the laws of nature and foretelling potentially lethal phenomena, the history of modeling and its prospects for success in the future, and the enormous challenges to scientific prediction posed by the chaos phenomenon, which is the high instability that underlies many processes around us.
Glimpsing the future -- Walls of water : tsunamis -- Land in upheaval : earthquakes -- Chimneys of hell : volcanic eruptions -- Giant whirlwinds : hurricanes, cyclones, and typhoons -- Mutant seasons : rapid climate change -- Earth in collision : cosmic impacts -- Economic breakdown : financial crashes -- Tiny killers : pandemics -- Models and prediction : how far can we go?
Includes bibliographical references (p. [189]-192) and index.
Keywords: Natural disasters -- Forecasting; Human beings -- Effect of climate on; Climatic changes -- Social aspects